2021
DOI: 10.3389/fenvs.2021.703029
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Eggs and Spawning Zones of Hairtail Fishes Trichiurus (Pisces: Trichiuridae) in Northern South China Sea, Using DNA Barcoding

Abstract: Commercially important hairtails, Trichiurus spp., are widely distributed throughout China’s marine waters. Because eggs of these species are difficult to identify and the taxonomy of the group has recently been resolved, their spawning grounds in the northern South China Sea (SCS) are not well known. We identified three Trichiurus species (T. japonicus, T. nanhaiensis, and T. brevis) using DNA barcodes in spring and late summer–autumn ichthyoplankton surveys of 2019 in the northern SCS. Egg distributions reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 57 publications
2
10
0
Order By: Relevance
“…A previous study in Trichiurus species suggests a genetic well mixture and a lack of distribution barrier for T. nanhaiensis 17 . Ocean currents, which change with the monsoon and are highly variable in the SCS, play an important role in transporting eggs, larvae, or juveniles of T. nanhaiensis 40 , 41 . We suggested that the high dispersal ability of marine fish may be appeared by gene flow following divergence, indicating that divergent mitochondrial lineages arose within a panmictic population.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in Trichiurus species suggests a genetic well mixture and a lack of distribution barrier for T. nanhaiensis 17 . Ocean currents, which change with the monsoon and are highly variable in the SCS, play an important role in transporting eggs, larvae, or juveniles of T. nanhaiensis 40 , 41 . We suggested that the high dispersal ability of marine fish may be appeared by gene flow following divergence, indicating that divergent mitochondrial lineages arose within a panmictic population.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Jaureguizar et al (2004) proposed that the major aims of fish migrations are related to seasonal (e.g., Trichiurus lepturus and Discopyge tschudii) and reproductive needs (e.g., Micropogonias furnieri, Mustelus schmitti, and Cynoscion guatucupa). Previous studies have suggested that temperature and salinity have the strongest influence on the seasonal structure of species composition (Jaureguizar et al, 2004;Liu et al, 2020;Hou et al, 2021). Thus, our study will investigate the migration patterns of each Trichiurus species along the coastline of China and whether these migrations are shaped by environmental factors, including ocean currents.…”
Section: Introductionmentioning
confidence: 98%
“…Eggs represent the earliest phase in the life cycle of fish. Because eggs cannot move unaided, they can provide valuable information about the reproductive biology, preferred spawning times, spawning sites, and recruitment success rates within fish populations (Baumgartner et al, 2004;Cao et al, 2007;Hou et al, 2021a;Takeuchi et al, 2021). Information on the composition and spatial and temporal distribution of fish eggs is vital for determining closed fishing zones, fishing moratoriums, fishery resource management strategies, marine protection areas, and even environmental evaluation of sea/fresh water-related construction and engineering (Rakocinski et al, 1996;Cao et al, 2007;Oliveira and Ferreira, 2008;Ahern et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Information on the composition and spatial and temporal distribution of fish eggs is vital for determining closed fishing zones, fishing moratoriums, fishery resource management strategies, marine protection areas, and even environmental evaluation of sea/fresh water-related construction and engineering (Rakocinski et al, 1996;Cao et al, 2007;Oliveira and Ferreira, 2008;Ahern et al, 2018). Although the importance of the fish egg pool has been long recognized, species-level information on the occurrence of fish eggs and their distributional patterns is lacking because of the difficulties in identifying fish egg stages (Baumgartner et al, 2004;Bui et al, 2011;Burrows et al, 2018;Hou et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%